Analysis of the Surface Matrix of Copper Cable in Jointing as the Effect of Increasing Current and Heating on Fire Application - Hasugian, Supriedi; Hasan, Syafruddin; Rambe, Ali Hanafiah; Supiyani (Talenta Publisher, 2024)
This research aims to analysis of the surface matrix of copper cable in jointing as the imfluence of increasing current and heating on fire experiment. The investigation makes it easier to observe parts of its material of the surface matrix changes of copper cable in jointing as increasing of heating. The study was observed the material surface of general requirements for electrical installations (PUIL) jointed cables and standard NYA Ã¸ 1.5 mm2 cables at current load of 50 A and 110A using HIROX digital microscope, XRF (X-ray fluorescence), Raman spectroscopy, and fluke infrared thermometer (FLIR). The results of the study were obtained that the PUILsample jointing heat cable reached of 201oC and 1087oC with heat standard cable of 25.6oC. The copper cable will melt when the cable reached in over heating of 1080oC that it caused the deformation of the cross-sectional area of the cable which are observed in changes in the surface matrix of the burned cable structure. This research can be used as scientific basic for inverstigating the caused of fires and the heat maximum application on the cables.